Uterine adenomyosis in a Colombian Creole mare: Case report - Gallego Rodriguez, Renso Sneider (2020)
This report presents the case of an 18-year-old Colombian creole mare with a history of subfertility, continuous and prolonged oestrous, uterine oedema categorized between 4 and 5, and moderate sized cysts present in the endometrial and myometrial layer. As a diagnostic plan, an endometrial culture, hysteroscopy, and a biopsy for histopathology were performed. Proteus mirabilis was found in the bacteriology culture. Hysteroscopy showed abundant cysts on the body and uterine horns. In histopathology, hyperplasia of the endometrial glands with fibrotic foci and mononuclear infiltrate was evident. Therapy with antibiotics, dimethyl sulfoxide DMSO and infusion of platelet-rich plasma did not improve her condition and the mare did not recover her reproductive function.